Peroxiredoxin 1/2 protects brain against H2O2‐induced apoptosis after subarachnoid hemorrhage. Issue 2 (23rd October 2018) - Lu, Yue; Zhang, Xiang-Sheng; Zhou, Xiao-Ming; Gao, Yong-Yue; Chen, Chun-Lei; Liu, Jing-Peng; Ye, Zhen-Nan; Zhang, Zi-Huan; Wu, Ling-Yun; Li, Wei; Hang, Chun-Hua
ABSTRACT: Recent studies suggest that peroxiredoxin1/2 (Prx1/2) may be involved in the pathophysiology of post‐ischemic inflammatory responses in the brain. In this study, we assessed the distribution and function of Prx1/2 in mice after experimental subarachnoid hemorrhage (SAH). We investigated the distribution of Prx1/2 in the brains of mice both in vivo and in vitro using immunofluorescence staining. The expression of Prx1/2 after SAH was determined by Western blot. Adenanthin was used to inhibit Prx1/2 function, and Prx1/2 overexpression was achieved by injecting adeno‐associated virus. Oxidative stress and neuronal apoptosis were assessed both in vivo and in vitro . The neurologic function, inflammatory response, and related cellular signals were analyzed. The results showed that Prx1 was mainly expressed in astrocytes, and Prx2 was abundant in neurons. The expression of Prx1/2 was elevated after SAH, and their expression levels peaked before proinflammatory cytokines. Inhibiting Prx1/2 promoted neuronal apoptosis by increasing the hydrogen peroxide (H2 O2 ) levels via the apoptosis signal‐regulating kinase 1/p38 pathway. By contrast, overexpression of Prx1/2 attenuated oxidative stress and neuronal apoptosis after SAH. Thus, early expression of Prx1/2 may protect the brain from oxidative damage after SAH and may provide a novel target for treating SAH.—Lu, Y., Zhang, X.‐S., Zhou, X.‐M., Gao, Y.‐Y., Chen, C.‐L., Liu, J.‐P., Ye, Z.‐N., Zhang, Z.‐H., Wu, L.‐Y., Li, W., Hang, C.‐H. Peroxiredoxin 1/2 protects brain against H2 O2 ‐induced apoptosis after subarachnoid hemorrhage. FASEB J. 33, 3051–3062 (2019). www.fasebj.org